Vestibulo-oral inclination of maxillary and mandibular canines and bicuspids: a CBCT investigation - Hourfar, Jan; Bister, Dirk; Lisson, Jörg A.; Goldbecher, Christine; Ludwig, Björn (Head & face medicine, 2016)
The aim of this retrospective study was to measure tooth and crowns axes of canines, first and second bicuspids of orthodontically untreated subjects with near normal occlusion to: 1. Define norms and reveal potential gender differences and 2. Discuss implications of the findings for orthodontics.
Gesehen am 20.05.2020